Sadness, hopelessness and suicide attempts in bullying: Data from the 2018 Iowa youth survey - Kaela L. Newman; Daniel S. Alexander; John P. Rovers (PLoS ONE, 2023)
Background Bullying in schools is a common problem that can have significant consequences on the mental health of both bullies and victims of bullying. Some estimates suggest that 30% of American youth are bullied. Self-reported incidence of depression, anxiety, and suicide attempts has been correlated with bullying. Victims may also suffer from a variety of somatic complaints such as headache, sleep disorders, and others. Youth surveys undertaken by Education or Public Health Departments in most US states are an underutilized resource in evaluating the problem and any consequences. Objective The objective of this study was to explore the association of being involved in bullying either as a victim and/or a bully on mental health and suicide ideation by analyzing data from the 2018 Iowa Youth Survey. The results will then be applied to the published anti-bullying literature to make suggestions for how anti-bullying programs may be designed. Methods Data were obtained from the 2018 Iowa Youth Survey (IYS), which is a cross-sectional survey of 6th, 8th and 11th grade students. We chose two mental health questions as dependent variables and used a multivariable logistic regression analysis to evaluate the correlation between the two dependent variables and ten types of bullying included in the IYS. Since some respondents in the IYS were prescribed psychotropic medications to help with feeling angry, anxious, nervous, or sad, we adjusted for the use of psychotropic medication in our analysis. Similarly, the literature suggests that some students are both bullies and victims (bully-victims). Accordingly, we also adjusted for bully-victims. Results Unadjusted Odds Ratios (ORs) showed that not all forms of bullying were correlated with a significant risk of mental distress. Physical bullying had comparatively little association (ORs < 1 or overlapped 1), while identity bullying on sexual orientation or gender identity or sexual joking was consistently correlated with significant ORs for feeling sad or hopeless and attempting suicide (ORs 1.40–2.84). Cyberbullying (ORs 1.32–1.70) and social bullying (ORs < 1–2.21) were correlated with mental distress with ORs generally between physical and identity bullying. When adjusting for medication use or bully-victim status, adjusted ORs (aORs) were generally lower than unadjusted ORs. Conclusions Not all types of bullying were significantly correlated with feeling sad or hopeless or attempting suicide. Being able to evaluate the specific associations of different types of bullying may have implications for teachers or policy makers hoping to implement bullying mitigation strategies in their schools.